Pola Asuh Anak pada Keluarga Broken Home di Kota Sungailiat Provinsi Bangka Belitung - Delvi Olivia; Mery Yanti; Yunindyawati Yunindyawati (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2017)
This study aims to analyze the parenting in a broken home, as well as to analyze the obstacles which is faced in taking care of a broken home children in Kota Sungailiat, Bangka Belitung province. This study uses the theory of social action of Max Weber. The method used in this study is a qualitative method. The research design isÂ case study. The location of this research is in Sungailiat Bangka Belitung province because families experiencing divorce cases in the city is increasing each year. Determining the informants is done purposively. The unit of analysis used in a broken home. Data collection techniques used were observation, interview, and documentation. In this study, the research strategy used is intrinsic case studies. Technique of checking and validity of data which are used are triangulation source, triangulation method, and triangulation of time. Data analysis technique is process analysis before being in the field and data analysis in the field which are data reduction, data presentation, and conclusion or verification. In summary the results of this research is that parenting in a broken home family, the parents give varied parenting such as authoritarian, democratic and permissive parenting. Each broken home family caused by divorce in providing care to their children experiencing problems which are economic constraints, access to education, and the factor of the number of children.